Health-related quality of life of salvage prostate reirradiation using stereotactic ablative radiotherapy with urethral-sparing - Greco, Carlo; Pares, Oriol; Pimentel, Nuno; Louro, Vasco; Nunes, Beatriz; Kociolek, Justyna; Marques, Joao; Fuks, Zvi (Frontiers in Oncology, 2022)
Purpose To explore whether prostate motion mitigation using the rectal distension-mediated technique is safe and effective in stereotactic ablative radiation therapy (SABR) salvage treatment of intraprostatic cancer recurrences following initial radiotherapy for primary prostate cancer. Materials and methods Between July 2013 and December 2020, 30 patients received salvage SABR for 68Ga- PSMA-11 PET/CT-detected intra-prostatic relapses. Median time from primary RT to salvage reirradiation was 70.2 (IQR, 51.3-116.0) months. Median PSA at retreatment was 3.6 ng/mL (IQR, 1.9-6.2). Rectal distension-mediated SABR was achieved with a 150-cm3 air-inflated endorectal balloon and a Foley catheter loaded with 3 beacon transponders was used for urethra visualization and on-line tracking. MRI-based planning employed a 2-mm expansion around the planned target volume (PTV), reduced to 0-mm at the interface with critical organs at risk (OARs). Volumetric Modulated Arc Therapy (VMAT) permitted a 20% dose reduction of the urethra. VMAT simultaneous integrated boost (SIB) of the dominant intraprostatic lesion was deployed when indicated. Median SABR dose was 35 Gy (7 Gy per fraction over 5 consecutive days; range 35-40 Gy). Toxicity assessment used CTCAE v.4 criteria. Results Median follow-up was 44 months (IQR, 18-60). The actuarial 3- and 4-year biochemical relapse free survival was 53.4% and 47.5%, respectively. Intraprostatic post-salvage relapse by PSMA PET/CT was 53.3%. Acute grade 2 and 3 genitourinary (GU) toxicities were 20% and 0%, respectively. There were no instances of acute grade ≥2 rectal (GI) toxicity. Late grade 2 and 3 GU toxicities occurred in 13.3% and 0% of patients, respectively. There were no instances of grade ≥2 late rectal toxicity. Patient-reported QOL measures showed an acute transient deterioration in the urinary domain 1 month after treatment but returned to baseline values at 3 months. The median IPSS scores rose over baseline (≥5 points in 53% of patients) between month 6 and 12 post-treatment as a result of urinary symptoms flare, eventually receding at 18 months. The bowel domain metrics had no appreciable changes over time. Conclusion Pursuit of local control in intraprostatic failures is feasible and can be achieved with an acceptably low toxicity profile associated with effective OAR sparing.